KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI INPRES DOYO LAMA KABUPATEN JAYAPURA PROVINSI PAPUA - Dike, Yosina; Dwikurnaningsih, Yari; Satyawati, Sophia Tri (Consilium: Education and Counseling Journal, 2024)
Principal leadership is the ability to mobilize existing resources in a school which will be used optimally to achieve the expected goals. In this study, the main objective is to describe how a principal improves teacher performance in leadership. Techniques to collect the data needed in this study use interview, observation, and documentation techniques. For data using interactive analysis models from Miles and Huberman, namely collecting data, data reduction, data presentation, and drawing conclusions. In this research, it produces a leadership style carried out by the principal, such as using a leadership style that is seen in the processes that the principal goes through in meeting activities, makes decisions, and acts in determining a solution or problem that arises. In principal leadership, the principal is a reflection, motivator, and guide for teachers, students, and people involved in the school environment.